2017
DOI: 10.1007/s13187-017-1188-5
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Protective Behaviors About Skin Cancer Among Nursing Students in the West Black Sea Region of Turkey

Abstract: Skin cancer is an important health problem worldwide among cancer types and results in death at a minimum level in the case of early diagnosis. Therefore, the application of prevention programs is vital. Nurses by definition take responsibility for programs in prevention, early diagnosis, and screening for cancer. This study was conducted to determine the extent of skin cancer knowledge and protective behaviors among nursing students in the West Black Sea Region of Turkey. This cross-sectional, descriptive stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 22 publications
2
16
0
1
Order By: Relevance
“…Most medical professionals were aware of the harmful effects of UVR in relation to skin cancer . Isvy et al .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Most medical professionals were aware of the harmful effects of UVR in relation to skin cancer . Isvy et al .…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐eight per cent to 86% of different medical professionals applied sunscreen during sun exposure . Sixty‐one per cent of Turkish nurses reported that when buying sunscreen, the SPF of the sunscreen was their top consideration …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations